Benzenesulfonamides with different rigidity-conferring linkers as carbonic anhydrase inhibitors: an insight into the antiproliferative effect on glioblastoma, pancreatic, and breast cancer cells. (31st December 2022) - Liguori, Francesco; Carradori, Simone; Ronca, Roberto; Rezzola, Sara; Filiberti, Serena; Carta, Fabrizio; Turati, Marta; Supuran, Claudiu T.
Abstract: Among the chemotypes studied for selective inhibition of tumour-associated carbonic anhydrases (CAs), SLC-0111, a ureido-bearing benzenesulfonamide CA IX inhibitor, displayed promising antiproliferative effects in cancer cells in vitro and in vivo, being in Phase Ib/II clinical development. To explore the structural characteristics required for better discrimination of less conserved regions of the enzyme, we investigate the incorporation of the urea linker into an imidazolidin-2-one cycle, a modification already explored previously for obtaining CA inhibitors. This new library of compounds inhibited potently four different hCAs in the nanomolar range with a different isoform selectivity profile compared to the lead SLC-0111 . Several representative CA IX inhibitors were tested for their efficacy to inhibit the proliferation of glioblastoma, pancreatic, and breast cancer cells expressing CA IX, in hypoxic conditions. Unlike previous literature data on SLC-149, a structurally related sulphonamide to compounds investigated here, our data reveal that these derivatives possess promising anti-proliferative effects, comparable to those of SLC-0111 . Graphical Abstract: UF0001